Perceived Level of Job Satisfaction and its Relation to Employee Retention: The Case of a Philippine Government Agency - Donna M Errua; Jacob B Fabilane; Mark Garenz S Gonzales; Jesus Briones; Marmelo V. Abante (People and Behavior Analysis, 2025)
Job satisfaction is a key area of interest for competitive organizations, as it significantly influences the retention of skilled and committed employees. This study aimed to investigate the level of job satisfaction among employees, employee retention rates, and the relationship between job satisfaction and employee retention. Additionally, it sought to identify programs and benefits that could enhance job satisfaction and retention rates. This descriptive-correlation research used a researcher-structured questionnaire distributed to 70 full-time employees of the subject government agency in the Philippines. Statistical tests, including frequency, percentage, weighted mean, and Spearman's rank correlation test were employed in the data analysis. Findings revealed that employees are satisfied with their jobs, especially when it comes to compensation, job content, promotion, supervision, and relationships with colleagues. Additionally, the study emphasized that employees are more likely to remain in the organization. Moreover, the study concluded that the level of job satisfaction exhibits a positive and strong correlation with employee retention. The study also revealed that healthcare benefits are considered a major contributor to employees’ retention among the programs and benefits that an organization can provide. Finally, this study can serve as a model for other government agencies to enhance job satisfaction and productivity among employees, thereby contributing to long-term employee retention, that benefits both employees and the organization.